ANTI-TERMITE EFFECT OF ANADELPHIA AFZELIANA (RENDLE) STAPF EXTRACTS ON SELECTED WOOD SPECIES IN MAKURDI, BENUE STATE, NIGERIA - Okechukwu, G. C.; Agbidye, F. S.; Tembe, E. T.; Ekhuemelo, Dr. David Oriabure (FUDMA JOURNAL OF SCIENCES, 2020)
This study examined anti-termite effect of Anadelphia afzeliana extracts on Daniellia oliveri, Gmelina arborea and Terminalia ivorensis wood species in Makurdi, Nigeria. A. afzeliana was collected, dried under shade, pulverized and the phytochemical constituents of screened. Weight of 100 g was respectively dissolved in 200 mL of methanol and hot water and mixtures left to macerate within 24 hours and thereafter filtered to obtain extracts. Concentrations of 20 %, 30 % and 50 % were constituted from methanol and aqueous extracts.Test woods were weighed and impregnated in treatments for 72 hours, after which absorption and retention were calculated. Treated woods were laid out in a timber grave yard in a Completely Randomized Design with seven treatments and solignum as control. Grand total of 360 test wood were used. Percentage weight loss was calculated on test wood. Anthraquinones, balsams, flavonoids, phlobatannins, tannins, terpens, resins, phenols and saponins phytochemicals were present in A. afzeliana. Mean absorption  of G. arborea, T. ivorensis and D. oliveri test wood were 93.04 -130.55 kg/m3, 100.54 - 142.04 kg/m3 and 96.94 - 175.01 kg/m3, respectively. The values were lowest in solignum and highest in 20 % A. afzeliana aqueous extract. Mean retention in G. arborea, T. ivorensis and D. oliveri were 9.29 - 62.51 kg/m3, 11.29 - 90.78 kg/m3 and 10.79 - 55.69 kg/m3; lowest in solignum and highest in 50 % A. afzeliana aqueous extract. Mean percentage weight loss was 13.81 - 30.65 % (G. arborea), 13.37 - 23.31 % (D.  oliveri) and
Keywords: Absorption, A. afzeliana, extract, retention, termites, weight loss